Enhanced Fingerprint Recognition Techniques (International Journal of Engineering and Computer Science, 2015)
Fingerprints have been used for over a century and are the most widely used form of biometric identification. Fingerprint image enhancement is required to make the image clearer for subsequent operations The quality of fingerprint images is not completely perfect. Images may be corrupted and damaged due to some skin conditions so there is a need to improve the quality of images. In this paper a new technique is proposed which is based on various existing techniques. The proposed work is based on CLAHE, curve gabor filter and fourier filtering.. This paper presents a methodology and new implementation techniques for fingerprint image enhancement.